Glucagon-like peptide-1 receptor agonists in neoplastic diseases - Ji, Lisan; He, Xianzhen; Min, Xinwen; Yang, Handong; Wu, Wenwen; Xu, Hao; Chen, Jun; Mei, Aihua (Frontiers in Endocrinology, 2024)
Glucagon-like peptide-1 receptor agonist (GLP-1RA), a novel hypoglycemic agent for the treatment of type 2 diabetes, has well-known effects such as lowering blood sugar, ameliorating inflammation, reducing weight, and lowering blood lipids. It has also been shown that it can influence the proliferation and survival of cells and has a certain effect on the prognosis of some neoplastic diseases. In this study, the potential effects of GLP-1RAs on the occurrence and development of tumors were reviewed to provide new ideas for the prevention and treatment of tumors in patients.